2008
DOI: 10.1016/j.jpcs.2008.04.016
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of the zircon-reidite pressure induced transformation

Abstract: To cite this version:M. Marqués, J. Contreras-García, M. Flórez, J.M. Recio. On the mechanism of the zircon-reidite pressure induced transformation. Journal of Physics and Chemistry of Solids, Elsevier, 2009, 69 (9) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 19 publications
(26 reference statements)
2
15
0
Order By: Relevance
“…According to previous experimental studies performed under the ambient condition, zircon should have an indirect band gap of 6.5 eV [35], which provides the properties of good gate dielectric materials. Our LDA calculations, though underestimates the electronic band gap yielded a value 4.79 eV which agrees fairly well with earlier theoretical data [12]. The calculated band gaps of reidite and wolframite are 4.36 eV and 4.58 eV, respectively.…”
Section: Structure and Eossupporting
confidence: 91%
See 2 more Smart Citations
“…According to previous experimental studies performed under the ambient condition, zircon should have an indirect band gap of 6.5 eV [35], which provides the properties of good gate dielectric materials. Our LDA calculations, though underestimates the electronic band gap yielded a value 4.79 eV which agrees fairly well with earlier theoretical data [12]. The calculated band gaps of reidite and wolframite are 4.36 eV and 4.58 eV, respectively.…”
Section: Structure and Eossupporting
confidence: 91%
“…They suggested a transition to the wolframite type phase at 56 GPa. The transition T 1 leads to a significant volume collapse of 9.45% [12] in ZrSiO 4 structure, which is much less for the transition T 2 (2.43 %) (Fig. 6b).…”
Section: Stability and Phase Transitionmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, the more stable high-pressure polymorph of zircon crystallizes in the scheelite-type structure by reducing $ 10% the unit cell volume across the transition. This is believed to occur via a martensitic-phase transformation, that is, there exist a subtle but rapid rearrangement of atomic positions nonetheless in a cooperative way since the coordination of the A and B cations, bisdisphenoids-[AO 8 ] and tetrahedral- [BO 4 ] respectively, do not change through the transition [6,7]. However, the microscopic mechanism, that is, displacive or reconstructivemodel, remains highly controversial [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Grzechnik et al, 2003), is a tetragonal 8À4 coordinated mineral found in hydrothermal veins and skarns, where it is commonly associated with wolframite and other large cation refractory minerals. The scheelite structure is shared by relatively few minerals; examples include stolzite, PbWO 4 , wulfenite, PbMoO 4 , powellite, CaMoO 4 and reidite, a high pressure ZrSiO 4 (zircon) polymorph that is found in impact breccias (Reid and Ringwood, 1969;Liu, 1979;Marques et al, 2009). Raspite is a polymorph of stolzite, but it is structurally unique with no other composition sharing its topology in any conditions (Fujita et al, 1977).…”
Section: Introductionmentioning
confidence: 99%